2019
DOI: 10.1177/0888406419873060
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Preservice Teachers’ Self-Efficacy and Beliefs About Inclusive Education

Abstract: Teachers’ self-efficacy and beliefs are important to classroom practices and student success. In this study, the authors examine preservice teachers’ self-efficacy and beliefs related to inclusive education. One hundred seventy-nine preservice teachers enrolled in secondary or elementary education programs participated in this study. Overall, participants in elementary versus secondary programs felt more responsible for students with disabilities and more efficacious with inclusive practices. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…There is no consensus regarding the influence of gender on PT's attitudes toward inclusion. While studies have not observed significant differences by gender (Haq and Mundia, 2012;O'Toole and Burke, 2013;Sharma and Nuttal, 2016;Metsala and Harkins, 2020), others report that the female gender is associated with more positive attitudes (Forlin et al, 2009;Ahsan et al, 2012;Specht et al, 2016;Subban and Mahlo, 2017), and only one reported that male PT holds more positive attitudes (Opoku et al, 2021).…”
Section: Influence Of Pre-service Teachers' Individual Characteristicsmentioning
confidence: 96%
“…There is no consensus regarding the influence of gender on PT's attitudes toward inclusion. While studies have not observed significant differences by gender (Haq and Mundia, 2012;O'Toole and Burke, 2013;Sharma and Nuttal, 2016;Metsala and Harkins, 2020), others report that the female gender is associated with more positive attitudes (Forlin et al, 2009;Ahsan et al, 2012;Specht et al, 2016;Subban and Mahlo, 2017), and only one reported that male PT holds more positive attitudes (Opoku et al, 2021).…”
Section: Influence Of Pre-service Teachers' Individual Characteristicsmentioning
confidence: 96%
“…(Jamie L. Metsala, 2019) carried out study on preservice teachers' self-efficacy and beliefs related to inclusive education, examined 179 enrolled in secondary or elementary education and discussed the results within the context of preparing teachers for the inclusive classroom. The previous studies on how organizations could retain their employees reveal that organizations face the challenge of retention good employees.…”
Section: Aspects Of Job Satisfactionmentioning
confidence: 99%
“…Despite the number of inclusion students having increased rapidly over the past 20 years, researchers have argued that the inclusion approach is still not being applied in practice as it ought to be (Melekoglu et al, 2009;Moberg et al, 2020;Rakap & Kaczmarek, 2010;Zagona et al, 2017), since teachers from different disciplines do not generally possess the specific teaching skills required for the inclusive educational setting. A growing number of studies have highlighted the need for both preservice and inservice teachers to develop the necessary teaching skills for the inclusive educational setting (Andrews, 2002;Florian, 2014;Laarhoven et al, 2006;Metsala & Harkins, 2019;Moberg et al, 2020;Sharma et al, 2008;). In order to provide meaningful inclusion practices, teacher effect and high quality differentiated instruction for individuals with disabilities is considered as being amongst the factors most significant for student learning (Rockoff, 2004;Sanders et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide meaningful inclusion practices, teacher effect and high quality differentiated instruction for individuals with disabilities is considered as being amongst the factors most significant for student learning (Rockoff, 2004;Sanders et al, 1997). However, many general education teachers struggle to provide meaningful inclusive practices in the general education classroom (De Boer et al, 2011;Metsala & Harkins, 2019;Moberg et al, 2020). Researchers have underlined that preservice teacher programs need to consider alternative approaches in order for preservice teachers to receive the correct support, guidance, and encouragement during their teacher education programs and into their early careers (Ambrosetti & Dekkers, 2010;Hall et al, 2008;Hudson, 2013;Korhonen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation